Waste and Overconsumption in Modern Finance: an Analysis of Qs Values. Al-Isra: 26-27 - Arum, Hafidza Sanshia; Mawardi, Mawardi (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
Excessive consumption and wastefulness have become critical issues in modern finance, especially in the digital era that facilitates consumerist behavior through online shopping and easy access to credit. This article explores the impact of consumerist lifestyles on individual and global economic stability and its relevance to the Islamic prohibition of wastefulness as stated in QS. Al-Isra: 26-27. This study employs a qualitative descriptive approach using thematic exegesis to analyze the concept of israf in the Qur'an. Findings reveal that consumerist behaviors, such as impulsive buying and consumer debt, harm financial stability and psychological well-being while exacerbating social inequality. QS. Al-Isra: 26-27 offers moral guidance on prudent financial management, avoiding wastefulness, and prioritizing social responsibility. This article emphasizes the importance of Islamic finance education, the use of Islamic financial technology, and the application of maqasid shariah principles to establish a sustainable economic system. Hence, Islamic values can serve as an effective solution to address the challenges of consumerist lifestyles in the modern era.